2001
DOI: 10.1038/87974
|View full text |Cite
|
Sign up to set email alerts
|

Whole recombinant yeast vaccine activates dendritic cells and elicits protective cell-mediated immunity

Abstract: There is currently a need for vaccines that stimulate cell-mediated immunity-particularly that mediated by CD8+ cytotoxic T lymphocytes (CTLs)-against viral and tumor antigens. The optimal induction of cell-mediated immunity requires the presentation of antigens by specialized cells of the immune system called dendritic cells (DCs). DCs are unique in their ability to process exogenous antigens via the major histocompatibility complex (MHC) class I pathway as well as in their ability to activate naive, antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(169 citation statements)
references
References 22 publications
6
158
2
Order By: Relevance
“…The potential for carbohydrate patterning to increase antigenic potency has led to novel approaches to vaccine development. Examples include chemically conjugating mannans from S. cerevisiae to weak Ags (56), expressing recombinant proteins in S. cerevisiae (57), and targeting of DEC-205 with mAbs coupled to peptides (58). Thus, our data demonstrating that efficient T cell responses to MP require recognition of terminal mannose groups by mannose receptors provide both a molecular basis for the immunogenicity of cryptococcal MP and support for vaccination strategies that target MR members.…”
Section: Discussionmentioning
confidence: 81%
“…The potential for carbohydrate patterning to increase antigenic potency has led to novel approaches to vaccine development. Examples include chemically conjugating mannans from S. cerevisiae to weak Ags (56), expressing recombinant proteins in S. cerevisiae (57), and targeting of DEC-205 with mAbs coupled to peptides (58). Thus, our data demonstrating that efficient T cell responses to MP require recognition of terminal mannose groups by mannose receptors provide both a molecular basis for the immunogenicity of cryptococcal MP and support for vaccination strategies that target MR members.…”
Section: Discussionmentioning
confidence: 81%
“…DCs also possess the unique ability to process particulate Ags efficiently into the MHC class I pathway, referred to as cross-presentation (42). Interestingly, it has been recently reported that whole recombinant yeast can activate DCs, which elicit protective cell-mediated antitumor immunity via CD4 Ļ© and CD8 Ļ© T lymphocytes (43). DC-SIGN binds yeast-derived mannan with a high affinity, indicating that DC-SIGN could be involved in yeast uptake.…”
Section: C-type Lectins As Ag Receptors On Dcsmentioning
confidence: 99%
“…A recent study showed that yeast cells could act as an efficient vaccine and elicited protective cell-mediated immunity by virtue of their ability to induce DC maturation, IL-12 production, and efficient priming for MHC class I-or II-restricted Ag-specific T cell responses (59). We show in this work that not only the yeasts but yeast RNA could be an efficient trigger of DC maturation, IL-12 production, and induction of protective Ag-specific responses to Candida.…”
Section: Figurementioning
confidence: 99%